B-scan measurement of optic nerve sheath diameter as a marker of elevated intracranial pressure - Raj, Gaurav; Singh, Ragini; Deodhar, Manish; Chauhan, Abhishek; Kumar, Tushant; Gaur, Manju (International Journal of Research in Medical Sciences, 2017)
Background: Elevated intracranial pressure is a complication of several traumatic as well as non-traumatic medical conditions. Clinical diagnosis can be difficult as it may present with non-specific complaints such as headache, vomiting, blurred vision, vomiting and altered sensorium. The expertise to perform ophthalmoscopy is not always immediately available in emergency rooms and the access to cross sectional imaging may be limited. Distention of the optic nerve sheath is an early sign of raised ICP as it is in direct communication with the subarachnoid space. Ultrasound is a widely available tool in emergency situations which can be used to measure the optic nerve sheath diameter (ONSD). Methods: In this prospective observational study, 36 patients suspected of having elevated intracranial pressure underwent high resolution B-scan ultrasound to measure the ONSD. Further, patients underwent CT scan of head and were evaluated for signs of raised ICT. Sensitivity and specificity of B-scan measurement of ONSD with CT scan was compared. Results: The ONSD measurement was 88.5% sensitive (95% CI 68% to 97%) and 90% specific (95% CI 55% to 99%) with CT as the reference. Conclusions: Bedside ultrasound B-scan measurement of the optic nerve sheath diameter provides information about raised intracranial pressure with a high sensitivity and specificity.